Vikings of the steppe : Scandinavians, Rus', and the Turkic world (c. 750-1050) - Katona, Csete (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book explores the relationship between Vikings, Rus' and nomadic (mostly Turkic) steppe dwellers during the course of the Viking Age (c. 750-1050) in a geographical area stretching from Eastern Scandinavia through the Kievan Rus', Byzantium, the Islamic world to the Western Eurasian steppes. The primary focus is the steppe influence on the development of Scandinavian-Rus' culture. It illustrates the effects of Turkic (nomadic) cultures on the evolving Scandinavian-Rus' communities in their military technology and tactics, as well as in everyday customs, ritual traditions and religious perceptions, whilst paying attention to the politico-commercial necessities and possible communication channels tying these two cultures, normally considered to be distinct, together. The arguments are supported by a multi-disciplinary analysis of diverse historical and archaeological materials occasionally supplemented with linguistic evidence. The result is a comprehensive evaluation of the relations of the Scandinavians active in the 'East' had with Turkic groups, and bring (the so far neglected) steppes into Viking studies in general. The book will fill a serious scholarly gap in the field of Viking Studies and will be read by both academics and students interested in the archaeological and historical sources concerned with the traditions of the 'Eastern Vikings'"--
List of figures -- List of tables -- Preface and acknowledgements -- Chapter 1: Introduction -- Chapter 2: The steppe and the Viking world -- Chapter 3: Armed conflicts -- Chapter 4: Trade -- Chapter 5: Retinues -- Chapter 6: Customs and religion(s) -- Chapter 7: Communication -- Conclusions -- Bibliography -- Index.
Keywords: Vikings -- Russia; Vikings -- Eurasia; Civilization, Viking; Civilization, Turkic; Scandinavia -- Relations -- Russia; Scandinavia -- Relations -- Eurasia; Russia -- Relations -- Scandinavia; Eurasia -- Relations -- Scandinavia; HISTORY / Europe / Scandinavia; HISTORY / Europe / Eastern